Data mining for municipal financial distress prediction - Alaminos Aguilera, David; Fernández, David; García-Lopera, Francisca; Fernández, Manuel Ángel (My University, 2018)
Data mining techniques are capable of extracting valuable knowledge from large and variable databases. This work proposes a data mining method for municipal financial distress prediction. Using a new proxy of municipal financial situation and a sample of 128 Spanish municipalities, the empirical experiment obtained satisfactory results, which testifies to the viability and validity of the data mining method proposed for municipal financial distress prediction.
Keywords: Minería de datos (Informática); Financial distress prediction; Data mining; Municipalities; Individual classifiers; Local governments